2010
DOI: 10.1007/s11033-010-0334-5
|View full text |Cite
|
Sign up to set email alerts
|

The molecular characterization and associations of porcine cardiomyopathy asssociated 5 (CMYA5) gene with carcass trait and meat quality

Abstract: The cardiomyopathy associated 5 (CMYA5) gene was also called TRIM76, which was belonged to the tripartite motif super family of proteins (TRIM). It was a direct transcriptional target for MEF2A and it played an important role in myofibrillogenesis. In the present study, a 12056 bp cDNA sequence of the porcine CMYA5 gene was obtained by RT-PCR. The sequence encoded a large protein consisting of 4003 amino acids and the carboxyl terminus of the predicted CMYA5 protein comprised of a B-box coiled-coil, two fibron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…TRIM24 belongs to the superfamily of tripartite motif-containing proteins which have a role in the immune system. A member of this protein family, TRIM76 , was reported to be highly expressed in porcine skeletal muscle and significantly associated with carcass traits such as ham percentage and intramuscular fat [61]. The results of our meta-analysis suggested that ELMO1 , which is associated with the development and progress of diabetes nephropathy in humans, is a candidate gene for CONF [62].…”
Section: Discussionmentioning
confidence: 99%
“…TRIM24 belongs to the superfamily of tripartite motif-containing proteins which have a role in the immune system. A member of this protein family, TRIM76 , was reported to be highly expressed in porcine skeletal muscle and significantly associated with carcass traits such as ham percentage and intramuscular fat [61]. The results of our meta-analysis suggested that ELMO1 , which is associated with the development and progress of diabetes nephropathy in humans, is a candidate gene for CONF [62].…”
Section: Discussionmentioning
confidence: 99%
“…A study examining gene expression differences in metabolism and function between intramuscular and subcutaneous adipocytes in cattle found that SCD was highly expressed in adipocytes and closely associated with fat formation [34]. CMYA5 gene can act as a potential candidate gene affecting pig meat quality [35]. Among the DELs, we found that MSTRG.13347.…”
Section: Identi Cation Of Differentially Expressed Mrnas and Lncrnasmentioning
confidence: 82%
“…Another associated gene is sideroflexin family and targeted to the mitochondrial membrane. In sheep, this gene and as important in the carrier molecule and related to the regeneration of pancreatic endocrine cells (Xi et al, 2011 described as correlated with meat quality in pigs (Xu et al, 2011), due the traits drip loss and intramuscular fat. that may play an important role in the hydrolysis of circulating peptides.…”
Section: Me Carvalhomentioning
confidence: 99%
“…In sheep, this gene and as important in the carrier molecule and related to (Xi et al, 2011). The pigs (Xu et al, 2011), due the traits drip loss and intramuscular fat. CPQ is a protein coding gene that may play an important role in the hydrolysis of circulating peptides.…”
Section: Me Carvalhomentioning
confidence: 99%
See 1 more Smart Citation